Singapore Convention: Should Indonesia Ratify It? - Rifa'i, Ahmad; Ramadhansyah, Dimas (Indonesian Journal of International Law, 2024)
As cross-border trading develops, there is an increasing need for an effective dispute resolution system to solve disputes on business transactions. Mediation is a well-established method of efficient alternative dispute resolution that was recently internationally recognized under a specific treaty. The United Nations General Assembly took a resolution to adopt the United Nations Convention on International Settlement Resulting from Mediation (“Singapore Convention”). The Indonesian government has tried to boost foreign investment, but such efforts have been delayed due to a legal enforcement issue, which requires a legal reform to provide certainty for investors by providing a seamless and internationally recognized dispute resolution system. Using a descriptive method on the Singapore Convention and the presence of mediation in Indonesia, this paper will analyze how Indonesia currently recognizes foreign dispute resolution decision under an arbitration system and not any other mechanisms, including mediation, as one of the primary options of an alternative dispute resolution. Therefore, there is an urgency for Indonesia to ratify the Singapore Convention.